Robot Pengenal Warna dengan Penganturan Kecepatan Menggunakan Metode PID - Mutiara, Andira; Nurhaliza, Rahmi; Dwisaputra, Indra; Yudhi, Yudhi (Jurnal Inovasi Teknologi Terapan, 2025)
This research focuses on the development of a robot equipped with a color recognition system and speed control using a PID controller. The robot employs a TCS3200 color sensor to detect object colors and determine its movement trajectory. The optimal distance between the sensor and the object was identified as 0.5 cm to ensure maximum accuracy. The PID controller is responsible for regulating the motor speed, ensuring the robot moves according to the specified velocity. At a setpoint of 100, the tuning parameters Kp 1.0, Ki 0.0012, and Kd 0.00045 produced a balance between fast response and stability. With a setpoint of 200, the tuning values Kp 1.0, Ki 0.0002, and Kd 0.0005 maintained both quick response and stability. For a setpoint of 300, the configuration of Kp 1.0, Ki 0.00035, and Kd 0.00070 achieved a balanced response with minimal overshoot. The test results demonstrate that the robot is capable of following color-based paths according to the predetermined speed settings.